Troublesome Triangles

Geometry Level 4

If a cos A + b cos B + c cos C a sin B + b sin C + c sin A \displaystyle a\cos{A} + b\cos{B} + c\cos{C} \over \displaystyle a\sin{B} + b\sin{C} + c\sin{A} = a + b + c 9 R = \displaystyle\frac{a+b+c}{9R} . Then the triangle is-

Here a , b , c a , b , c are sides of triangle and A , B , C A , B , C are the angles of Triangle and R R the the circumradius of A B C \vartriangle ABC


Try more here

Obtuse angled Triangle Isoceles Triangle Right Angled Triangle Equilateral Triangle

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Neelesh Vij
Jan 14, 2016

We know that a sin A = b sin B = c sin C = 2 R \frac{a}{\sin{A}} = \frac{b}{\sin{B}} = \frac{c}{\sin{C}} = 2R . Plugging in values we get

R ( sin 2 A + sin 2 B + sin 2 C ) a × b 2 R + b × c 2 R + c × a 2 R \displaystyle R(\sin{2A} + \sin{2B} + \sin{2C}) \over \displaystyle a \times \frac{b}{2R} + b\times \frac{c}{2R} + c\times \frac{a}{2R} = a + b + c 9 R = \displaystyle \frac{a+b+c}{9R} .

Rearragging we get ( Using identity sin 2 A + sin 2 B + sin 2 C = 4 sin A sin B sin C \sin{2A} + \sin{2B} + \sin{2C} = 4\sin{A}\sin{B}\sin{C} where A + B + C = π A+B+C = \pi )

8 R 2 ( sin A sin B sin C ) = ( a + b + c ) ( a b + b c + c a ) 9 R \rightarrow 8R^{2}(\sin{A}\sin{B}\sin{C}) = \displaystyle \frac{(a+b+c)(ab+bc+ca)}{9R} .

Again using a sin A = b sin B = c sin C = 2 R \displaystyle \frac{a}{\sin{A}} = \frac{b}{\sin{B}} = \frac{c}{\sin{C}} = 2R

8 R 2 × a 2 R × b 2 R × c 2 R = ( a + b + c ) ( a b + b c + c a ) 9 R \rightarrow \displaystyle 8R^{2}\times \frac{a}{2R} \times \frac{b}{2R} \times \frac{c}{2R} = \displaystyle \frac{(a+b+c)(ab+bc+ca)}{9R}

On expanding we get

( b a 2 + b c 2 2 a b c ) + ( a b 2 + a c 2 2 a b c ) + ( c a 2 + c b 2 2 a b c ) = 0 \rightarrow (ba^{2} + bc^{2} - 2abc) + (ab^{2} + ac^{2} - 2abc) + (ca^{2} + cb^{2} - 2abc) = 0

b ( a c ) 2 + a ( b c ) 2 + c ( a b ) 2 = 0 \rightarrow b(a-c)^{2} + a(b-c)^{2} + c(a-b)^{2} = 0

This is only possible when a = b = c a=b=c . So the triangle is e q u i l a t e r a l \boxed{equilateral}

No need to expand in the last Step, see carefully it is actually A.M = H.M implying a = b = c!

Aniket Sanghi - 4 years, 4 months ago

From the symmetrical look of the equation we are tempted to think it to be Equilateral Triangle.
L e t S = a = b = c , A + B + C = 6 0 o , 2 R = S S i n 60 , R = S 3 . S o L . H . S . = 3 S 1 2 3 S S i n 60 = 1 3 . R . H . S . = 3 S 9 S 3 = 1 3 3 = 1 3 = L . H . S . T h u s i t I S a n E q u i l a t e r a l T r i a n g l e . Let\ S=a=b=c, \ \ A+B+C=60^o,\ \ 2R=\dfrac S {Sin60},\ \ \implies\ R=\dfrac S {\sqrt3}.\\ So\ \ L.H.S.=\dfrac{3*S*\frac 1 2}{3*S*Sin60}=\dfrac 1 {\sqrt3}.\\ R.H.S.=\dfrac{3*S}{ 9* \frac S {\sqrt3} }=\dfrac 1{\frac 3 {\sqrt3}}=\dfrac 1 {\sqrt3}=L.H.S.\\ Thus\ \ it\ \ IS\ \ an \ \ \color{#D61F06}{Equilateral Triangle.}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...